Component‐resolved diagnosis of wasp (yellow jacket) venom allergy. Issue 2 (18th January 2013) - Ebo, D. G.; Faber, M.; Sabato, V.; Leysen, J.; Bridts, C. H.; De, L. S.
Summary Background Wasp venom allergy is a potentially life‐threatening condition with serious consequences of diagnostic error. Objective To assess whether component‐resolved diagnosis, using non‐glycosylated recombinant allergen components from yellow jacket can add to the diagnosis of wasp venom allergy. Methods In total, 148 patients with a wasp (yellow jacket) allergy were included, 91 with unequivocal tests, 26 with double positivity of serum‐specific IgE (sIgE) to both venoms, 21 with discrepant sIgE and skin test results and finally 10 having their diagnosis only confirmed by basophil activation test (negative sIgE and skin test results). Specific IgE to recombinant species‐specific allergen components Ves v 1 and Ves v 5 from yellow jacket, Api m 1 from honeybee and Ves v 5 complemented wasp venom were tested by ImmunoCAP. Results Overall, combined use of sIgE to rVes v 1 and rVes v 5 allowed correct diagnosis in 139 of the 148 patients (94%) and rApi m 1 was demonstrable in only one patient. Supplementing the traditional yellow jacket allergosorbent with rVes v 5 allowed to correctly diagnose wasp allergy in patients sensitized to Ves v 5 but demonstrating a negative sIgE to wasp venom. Conclusion Component‐resolved diagnoses with the wasp‐specific recombinant allergen components Ves v 1 and Ves v 5 is a reliable method to diagnose yellow jacket allergy and can help to take out the sting of difficult cases. However, as the number of patients with doubt after conventional tests is small, larger collaborative studies are needed to draw more definitive conclusions. Whether the rVes v 5 supplemented yellow jacket allergosorbent constitutes an asset in the diagnostic management of wasp venom allergy remains to be further established.